2017
DOI: 10.1038/srep42314
|View full text |Cite
|
Sign up to set email alerts
|

A novel human artery model to assess the magnetic accumulation of SPIONs under flow conditions

Abstract: Magnetic targeting utilises the properties of superparamagnetic iron oxide nanoparticles (SPIONs) to accumulate particles in specified vasculature regions under an external magnetic field. As the behaviour of circulating particles varies depending on nanoparticle characteristics, magnetic field strength and flow dynamics, we established an improved ex vivo model in order to estimate the magnetic capture of SPIONs in physiological-like settings. We describe here a new, easy to handle ex vivo model of human umbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…These particles have a good biocompatibility profile, as well as good colloidal and blood stability, 31 and were successfully targeted to the specific artery region ex vivo under external magnetic field gradient. 17 To our knowledge, this is the first study to demonstrate the possibility of magnetic targeting of SPIONs at the wall of a large artery in a living rabbit. The histological analyses showed the accumulation of iron at the targeted regions, which confirmed our previous ex vivo data, and indicated that magnetic accumulation of this type of SPIONs is possible, at least in superficial and/or easily accessible arteries in vivo.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…These particles have a good biocompatibility profile, as well as good colloidal and blood stability, 31 and were successfully targeted to the specific artery region ex vivo under external magnetic field gradient. 17 To our knowledge, this is the first study to demonstrate the possibility of magnetic targeting of SPIONs at the wall of a large artery in a living rabbit. The histological analyses showed the accumulation of iron at the targeted regions, which confirmed our previous ex vivo data, and indicated that magnetic accumulation of this type of SPIONs is possible, at least in superficial and/or easily accessible arteries in vivo.…”
Section: Discussionmentioning
confidence: 84%
“…Our previous studies in an ex vivo artery models suggested that magnetic accumulation of certain types of SPIONs is possible even under arterial flow conditions. 17,18 Other preclinical studies indicated that SPION-loaded cells can be magnetically targeted to stented carotid arteries in vivo in order to prevent thrombosis and restenosis in a rat model. 19 By increasing the effective local doses of pharmaceutical agents, MDT may therefore represent a useful tool to improve the plaque stability and reduce inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it enables to manipulate the magnetic objects toward the specific organ or tissues of the body [112][113][114], resulting in increased drug concentration at the target tissue with low systematic toxicity. In general, the magnetic drug carrier is developed by adding highly permeable magnetic nanoparticles into a non-magnetic matrix [115][116][117], where usually the hydrophilic polymer is adopted [115,[117][118][119], due to its capability to 22 enhance the water solubility of hydrophobic drugs, extend the circulation of drugs in blood, and suppress or eliminate fast renal excretion.…”
Section: Magnetic-sensitive Hydrogelmentioning
confidence: 99%
“…where the solid and dash lines denote the distributions of the magnetic fields in the absence and presence of the magnetic hydrogel respectively. 112…”
Section: Performance Of the Magnetic Hydrogel Subject To Various Hydrmentioning
confidence: 99%